CURCULIGO LATIFOLIA DRYAND. EX W.T.AITON (POTENSI PEMANFAATAN SEBAGAI OBAT TRADISIONAL DAN PEMANIS ALAMI) - Marina Silalahi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
Curculigo latifolia (Hypoxidaceae) is a type of Indonesian Indogenous plant which is easily found in various landscapes such as gardens, forests and has started to be cultivated in yards. This study aims to explain the potential of C. latifolia as a natural sweetener and its use as a traditional medicine and its bioactivity. The research method was carried out using library research, especially articles that can be accessed online using the keywords C. latifolia, uses C. latifolia and bioactivity of C. latifolia. C. latifolia has a morphology similar to that of a small palm which is used as a source of fibre, confectionery and traditional medicine. In traditional medicine C. latifolia is used to treat cancer, diabetes mellitus, tumor, eye infections, bacterial infections, fever, osteoporosis, anti-obesity and cardiovascular injuries. The C. latifolia fruit and seeds have great potential to be developed as a natural sweetener instead of sugar. The sweet taste of C. latifolia fruit is related to the content of curculin protein and neoculin protein.